2022
DOI: 10.1155/2022/2297268
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Metformin Intervention Prevents Lipotoxicity-Induced Hepatocyte Apoptosis by Alleviating Oxidative and ER Stress and Activating the AMPK/Nrf2/HO-1 Signaling Pathway in db/db Mice

Abstract: Objective. Nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2DM) commonly coexist and act synergistically to drive adverse clinical outcomes. This study is aimed at investigating the effects of exercise intervention and oral hypoglycaemic drug of metformin (MET) alone or combined on hepatic lipid accumulation. To investigate if oxidative stress and endoplasmic reticulum stress (ERS) are involved in lipotoxicity-induced hepatocyte apoptosis in diabetic mice and whether exercise and/or MET alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Given the increases in lipids in the livers of db/db mice, the reported pro-inflammatory role of lipids [ 49 ], and the fact that hepatic inflammation is a known characteristic of db/db mice [ 27 , 44 ], we next evaluated inflammatory markers in the liver using Western blotting ( Figure 4 A). The quantitative results are presented in Figure 4 B–G.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increases in lipids in the livers of db/db mice, the reported pro-inflammatory role of lipids [ 49 ], and the fact that hepatic inflammation is a known characteristic of db/db mice [ 27 , 44 ], we next evaluated inflammatory markers in the liver using Western blotting ( Figure 4 A). The quantitative results are presented in Figure 4 B–G.…”
Section: Resultsmentioning
confidence: 99%
“…As an energy sensor, AMPK regulates energy balance, but has also been reported to protect against lipid-induced inflammation [ 84 ]. AMPK activation was proposed as the mechanism responsible for the decrease in hepatic lipotoxicity in db/db mice [ 49 ]. Thus, the reduced inflammatory state caused by the CMS121 diet may also be linked to AMPK activation, possibly in combination with the inhibition of FASN, which remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our trial showed that metformin combined with a low dose of TFDG was significantly more effective than a high dose of TFDG alone in reducing blood glucose and inhibiting oxidative stress. It has been reported that metformin combined with honey or exercise for the treatment of diabetes-related diseases is effective in reducing toxic side effects and results in better outcomes than interventions alone. , However, when the antioxidant pycnogenol is combined with metformin, it does not show a higher protective effect on diabetic heart complications than when it is used alone . It can be seen that the combination has different performances in different substances and different diabetic complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, we need to consider that circulating EVs total number can change in function of PE protocols and depends also on sex, age, and pathophysiological condition [ 72 ]. Moreover, it has been reported that oxidative stress can lead to MVBs (multi-vesicular bodies) degradation with consequent release of exosomes by stressed cells [ [73] , [74] , [75] ]. Since PE induces a general reduction in oxidative stress [ 76 , 77 ], we can hypothesize that our observed increase in size and decrease in the number of circulating particles could be due to a global decrease in the stress level of producing cells.…”
Section: Discussionmentioning
confidence: 99%